Toward Nanowire HBT: Reverse Current Reduction in Coaxial GaAs/InGaP n(i)p and n(i)pn Core‐Multishell Nanowires. Issue 1 (23rd November 2018) - Liborius, Lisa; Heyer, Fabian; Arzi, Khaled; Speich, Claudia; Prost, Werner; Tegude, Franz‐Josef; Weimann, Nils; Poloczek, Artur
Abstract : In this work the reduction of reverse currents in Au‐catalyzed, MOVPE grown coaxial GaAs nanowire diodes are reported. The reduction is achieved by introducing an interstitial, lattice‐matched i ‐InGaP shell (spacer) as tunneling barrier inside the junction, which also functions as a selective etch stop. With increasing spacer thickness, rectification ratios of >1.57 × 10 6 at ± 1.65 V, ideality factors of 1.3, and dark saturation current densities as low as 20 pA cm −2 are extracted, which are related to a reduced tunneling probability. Temperature‐dependent DC measurements of junctions with thin spacers show a correlation to a simple (trap‐assisted) tunneling model. With absolute reverse currents in the pA range down to −3 V bias, the improved diode is implemented as a collector‐base junction in a coaxial n(i)pn nanowire structure by growing an additional, outer n ‐doped InGaP shell as the emitter layer in a nanowire HBT. Abstract : The authors report on the reduction of reverse currents in coaxial GaAs nanowire diodes. The reduction is achieved by introducing an interstitial i‐InGaP shell as tunneling barrier inside the junction. Temperature‐dependent DC measurements of junctions with thin spacers show a correlation to a simple (trap‐assisted) tunneling model. Fundamental bipolar transistor functionality is demonstrated, consequently.